Mapping Iron Uptake by Spinach from Roots to leaves and Tracking Iron bioaccessibility of Spinach leaves and Isolated Chloroplasts. - Farmanfarmaian, Ardeshir (2024)
Iron (Fe) is one of the most essential micronutrient minerals for human health such that it forms part of enzymes synthesising amino acids, hormones, neurotransmitters and collagen. It is also utilised for production of respiratory pigments including haemoglobin and myoglobin. Fe-deficiency is one of the most prevalent global micronutrient deficiencies and affects one-third of the global population, with anaemia being the key symptom. This project aimed to map the flow of Fe from the growth matrix to the human digestive system via chloroplasts of spinach plants. A novel Hoagland nutrient solution containing all essential nutrients was produced in the laboratory and supplied to the spinach plants. Plants were grown in hydroponic system on perlite, under controlled conditions in a growing room. Once at maturity, they were harvested for experiments including in-vitro digestion and bioaccessibility of spinach chloroplast rich fractions (CRFs). In subsequent experiments, spinach plants were dosed with seven distinct external Na Fe-EDTA solution concentrations; 10, 25, 50, 75, 100, 150 and 200 µM of Fe. This process proved the variability of growth indicators including Fe contents per plant part, and DWs during the observed growth periods. A typical method used to model the dynamically changing quantities is the application of Ordinary Differential Equations (ODEs). The modelling work showed that Fe toxicity limits and Cmax (maximum rate of uptake) were never reached within this concentration range. Moreover, the maximum yields and Fe contents for both root and stem material were reached after dosing with 50, 75 up to 100 µM Fe in feed solution. However, at higher dosing concentrations of Fe (150 and 200 µM Fe), internal concentrations of Fe, in both leaves and roots were higher but the yield represented by dry weight of leaves was lower. This indicates that the toxicity limits might have been reached based on the morphological observation at 150 and 200 µM Fe in solution, and the roots experienced Fe stress. Finally, the Markov Chain Monte Carlo (MCMC), is the most effective way in determining the posterior distribution, which in turn compares the actual data to any given model. The digestion work showed that the bioaccessibility of Fe from powdered leaf material was higher than the CRF as a percentage of initial iron content. However, as an absolute amount, the bioaccessible iron from CRF, either heated or fresh, was significantly higher than that in leaves. This finding was further supported by the use of CRF materials which has been labelled with 57Fe. The bioaccessibility of 57Fe using the same in-vitro digestion model followed by dialysability method showed no significant differences in the bioaccessibility of 57Fe and total Fe in both FCRF and HTCRF. However, the absolute amount of bioaccessible 57Fe and total Fe was significantly higher in FCRF than HTCRF. Overall, this work proved the possibility of using a hydroponic system to maximise the iron content inside spinach leaves up to 300 mg/kg of dry weight. With the help of ascorbic acid addition, about 4.5% of this Fe can be bioaccessible for human consumption once consumed as fresh leaves. Heat treatment does reduce this bioaccessibility to 3.6%. Isolating the chloroplasts rich fraction can provide an iron dense material (up to 4 times higher than the leaves materials) which can give 1.6% of its Fe content as bioaccessible iron in case of soil grown spinach and about 6% of this Fe using hydroponically grown spinach.